Risk factor analysis and outcomes of heart transplant recipients infected by COVID-19 - Zhang, Lin; Chen, Sipeng; Zheng, Shanshan; Liu, Sheng; Rao, Chenfei; Liao, Zhongkai; Fang, Xiaonan; Hu, Xiaoying; Huang, Jie; Zheng, Zhe (Frontiers in Immunology, 2025)
ObjectiveThis study aims to evaluate the prevalence, clinical characteristics, severity, mortality, and outcomes of COVID-19 infection in heart transplant recipients, focusing on risk factors for severe disease.MethodsA retrospective, observational study was conducted on adult heart transplant patients (HTxs) at Fuwai Hospital from December 1, 2022, to February 28, 2023, with follow-up until May 30, 2024. Clinical data were collected via telephone surveys and medical records. Logistic regression analyses were conducted to explore risk factors for severe disease.ResultsIn total, 728 of the 916 HTxs were infected with COVID-19 (79.48%); the vaccination rate was 27.95%. Of infected cases, 56.18% were mild, 18.82% moderate, 19.26% severe, and 5.77% critical. Severe disease occurred in 25.00%, with a mortality rate of 4.54%. Logistic regression analyses revealed that age (OR 1.048, 95% CI 1.031-1.066, P<0.001), history of diabetes (OR 1.829, 95% CI 1.221-2.740, P=0.005), Chronic kidney disease stage≥3 (OR 2.557, 95% CI 1.650-3.963, P<0.001) and immunosuppressive regimens including sirolimus (OR 1.639, 95% CI 1.145-2.348, P=0.007) were independent risk factors for severe infection, while age (OR 1.102, 95% CI 1.053-1.154, P<0.001) and Chronic kidney disease stage≥3 (OR 6.342, 95% CI 2.980-13.499, P<0.001) were independent risk factors for post-infection mortality. COVID-19 vaccination (OR 0.169, 95% CI 0.039-0.733, P=0.018) was found to be a protective factor against post-infection mortality.ConclusionCOVID-19 vaccination is recommended for HTxs to reduce severe outcomes and mortality. Sirolimus use was independently associated with severe infection, highlighting the need for careful management of immunosuppression.